Keanekaragaman Ikan Karang dan Demersal di Kawasan Konservasi Perairan Tatoareng, Provinsi Sulawesi Utara - Paraeng, Pricilia; Sangari, Joudy R.R; Budiman, Johnny; Mandagi, Stephanus V.; Wuaten, Julius; Kumaseh, Eunike; Munib, Aflaha A.; Marliana, Isnaini (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2025)
The establishment of Marine Protected Area (MPA) aims to protect important ecosystems and habitats for fish resources. However, fisheries have not been a major focus in the management of the Tatoareng MPA. In addition, information about the economically important fishes catches landed in coastal villages within the MPA over the past few years is still unknown by various parties. Therefore, this study was conducted to identify species diversity, catch trends, and average size of reef and demersal fishes landed within the Tatoareng MPA. Data were collected at two fish landing sites during the period May 2019 to March 2024, using the method of direct recording of fish landed by fishers. From this study, 187 species of reef and demersal fish from 23 families were identified, with the dominance of species from the Ephinephelidae, Lutjanidae, and Lethrinidae families. The results of this study are expected to be a recommendation in developing the governance of the Tatoareng MPA, by making spesific of reef and demersal fish the target and indicator of the success of the management of the MPA.